Postprandial VLDL lipolysis products increase monocyte adhesion and lipid droplet formation via activation of ERK2 and NFκB - den Hartigh, Laura J. (American Physiological Society, 2013)
Postprandial lipemia is characterized by a transient increase in circulating triglyceride-rich lipoproteins such as very low-density lipoprotein (VLDL) and has been shown to activate monocytes in vivo. Lipolysis of VLDL releases remnant particles, phospholipids, monoglycerides, diglycerides, and fatty acids in close proximity to endothelial cells and monocytes. We hypothesized that postprandial VLDL lipolysis products could activate and recruit monocytes by increasing monocyte expression of proinflammatory cytokines and adhesion molecules, and that such activation is related to the development of lipid droplets. Freshly isolated human monocytes were treated with VLDL lipolysis products (2.28 mmol/l triglycerides + 2 U/ml lipoprotein lipase), and monocyte adhesion to a primed endothelial monolayer was observed using a parallel plate flow chamber coupled with a CCD camera. Treated monocytes showed more rolling and adhesion than controls, and an increase in transmigration between endothelial cells. The increased adhesive events were related to elevated expression of key integrin complexes including Mac-1 [α(m)-integrin (CD11b)/β(2)-integrin (CD18)], CR4 [α(x)-integrin (CD11c)/CD18] and VLA-4 [α4-integrin (CD49d)/β(1)-integrin (CD29)] on treated monocytes. Treatment of peripheral blood mononuclear cells (PBMCs) and THP-1 monocytes with VLDL lipolysis products increased expression of TNFα, IL-1β, and IL-8 over controls, with concurrent activation of NFkB and AP-1. NFκB and AP-1-induced cytokine and integrin expression was dependent on ERK and Akt phosphorylation. Additionally, fatty acids from VLDL lipolysis products induced ERK2-dependent lipid droplet formation in monocytes, suggesting a link to inflammatory signaling pathways. These results provide novel mechanisms for postprandial monocyte activation by VLDL lipolysis products, suggesting new pathways and biomarkers for chronic, intermittent vascular injury.